Pengembangan Media Pembelajaran IPA Berbantuan Aplikasi Flipbuilder - Triana, Dhia Ayu; Hermansah, Bambang; Ayu, Imelda Ratih (Social Science Academic, 2024)
English abstract in one paragraph, 1 space with italic style, no more than 200 words. Abstract contains: (1) main questions and background of the problems discussed; (2) research position; (3) how the question is discussed (method); and (4) the main results of the discussion / research. This research was conducted with the aim of developing science learning media assisted by the flipbuilder application for class V SD Negeri 1 Tanjung Rancing which is valid, practical and effective. This research is research that was developed using the ADDIE development model with several steps, namely Analysis, Design, Development, Implementation, Evaluation. The research subjects were fifth grade students at SD Negeri 1 Tanjung Rancing. The results of this study prove that the Flipbuilder Application Assisted Science Learning Media developed is declared valid with the results of expert validation assessments, namely Media Experts, Language Experts, Material Experts, the percentage results obtained are 84.31% in the Very Valid category. In the practicality assessment of science learning media obtained by the results of student response questionnaires in the small group and large group stages, a percentage result of 91.23% was obtained in the "Very Practical" category. The product effectiveness results obtained from the test results average the percentage of student effectiveness of 83.52%. Based on the results of the validation, the results of the practicality trials, and the results of the product effectiveness tests on fifth grade students of SD Negeri 1 Tanjung Rancing, it can be concluded that the Flipbuilder Application Assisted Science Learning Media is suitable for use in implementing learning in elementary schools.